African-american female stereotyping in The Secret Life of Bees - Pallín López, Carolina (Epos : Revista de filología, 2013)
The film that is being analyzed in this article, The Secret Life of Bees, offers a unique piece to work on. This motion picture is based on Sue Monk Kidd’s novel with the same title published in 2003, and was directed by one of the very few African-American women directors, Gina Prince-Bythewood. This story puts forth an unusual depiction of the way African-American women have traditionally been portrayed. One of the key elements that contributes to this rare representation is the «Magical Negro» character in the movie, which has a tradition of being represented by men. The aim of this article is to analyze the way the «Magical Negro» character (August Boatwright) is introduced in The Secret Life of Bees, together with the other female characters (Lily Owens, Rosaleen Daise, June Boatwright and May Boatwright). I will also analyze how these representations contribute or shatter female African-American stereotypes. This film introduces a wide range of icons that go from the illiterate slave to the independent business owner, offering in this way a great piece to examine. This article will constitute an interdisciplinary inquiry which will take into account Gender Studies, Stereotyping, Cultural Studies and African American Studies. El filme que se analiza en este artículo, The Secret Life of Bees, nos ofrece una obra única para examinar. Dicha película está basada en la novela con el mismo título escrita por Sue Monk Kidd, publicada en 2003, y dirigida por una de las pocas directoras afroamericanas, Gina Prince-Bythewood. Esta historia nos muestra una imagen inusual de la mujer afroamericana si se compara con la forma en que tradicionalmente se ha escenificado dicho colectivo. Uno de los elementos clave que contribuye a tal representación es el personaje «Magical Negro» en la película, el cual tradicionalmente ha sido personificado mediante personajes masculinos. El objetivo de este artículo es analizar la forma en que el personaje «Magical Negro» (August Boatwright) es presentado en The Secret Life of Bees junto con el resto de personajes femeninos (Lily Owens, Rosaleen Daise, June Boatwright, May Boatwright). También analizaré las formas en que tales iconos contribuyen o crean una ruptura con respecto a los estereotipos femeninos afroamericanos. Esta cinta muestra una amplia gama de representaciones que van desde la esclava analfabeta hasta la mujer independiente dueña de su propio negocio, ofreciéndonos de esta forma una obra excepcional con la que trabajar. El presente artículo constituye un estudio interdisciplinar que tendrá en cuenta los estudios afroamericanos, de género, de estereotipia y culturales.